(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this paper, we establish a generalized fixed-point theorem for fuzzy contractions in fuzzy metric spaces. The result extends the well-known Banach contraction principle into the setting of fuzzy metric spaces by employing a generalized fuzzy contraction. Examples are provided to demonstrate the applicability and generalization of classical fixed-point results. Fuzzy fixed-point techniques are used in mathematical modelling to solve problems where traditional methods fail due to imprecise or uncertain data. To obtain fuzzy fixed points, different contraction conditions are implemented in a fuzzy context.